Ethics Toward Nature in View of Seyyed’s Ecosophy Hossein Nasr - Fauzi, Ramdani; Haidar, Muhammad (Jurnal Riset Agama, 2023)
This research aims to discuss the environmental crisis that occurs almost all over the world. This research uses a library research approach that contains descriptions of theories, findings and research materials obtained from reference materials to make the basis of research.Â The results of this study show that the cause of global environmental damage is due to the influence of the reductionist and exploitative western scientific paradigm. Descartes' philosophy that separates the spirit from the body and Newton's mechanistic physics that considers every organism can be known by separating it into small parts like a machine make science dry of spiritual things. Humans are an integral unit and cannot be separated from this nature, awareness of the position of humans in nature as caliphs who must maintain and preserve nature is the main key in handling this natural damage. Nasr provides a solution with Scientia Sacra, which is sacred knowledge that involves revelation which is the heart of knowledge and it is the center of this environment that includes and determines tradition.Â